LASER INDUCED-BREAKDOWN SPECTROSCOPY (LIBS): HISTÓRICO, FUNDAMENTOS, APLICAÇÕES E POTENCIALIDADES - Costa,Vinicius C. (2019)
This review attempts to present a broad view of the technique laser-induced breakdown spectroscopy (LIBS), since its origin, fundamentals, sample preparation strategies, use of chemometric tools for data processing, the advantages and limitations with regard to qualitative and quantitative analysis, aplications and future trends as an analytical technique that is in consolidation in analytical chemistry. LIBS is a rapid and versatile, which is able of providing qualitative and quantitative analytical information for practically any sample, in a virtually non-destructive way, without any substantial sample preparation. The instrumentation is simple, robust, compact, and enables remote analysis. The advancement of the LIBS applications in the areas of agriculture, environmental, food, biological/pharmaceutical, forensic, metallurgy and electronic waste were discussed in detail in this review. We consider that this review will be an important tool concerning dissemination of the LIBS, mainly for audience of undergraduate courses, and disciplines related to instrumental analysis.